Hubungan Pengetahuan, Sikap, dan Perilaku Masyarakat terhadap Pencegahan Diabetes Mellitus - Zubiyan Munandar; Doni Frimawan (Journal of Applied Health Sciences, 2025)
Diabetes mellitus is a major public health problem with a steadily increasing prevalence globally and nationally. The prevention of this disease largely depends on the community’s level of knowledge, attitudes, and practices. This study aims to analyze the relationship between knowledge, attitudes, and practices toward diabetes mellitus prevention. A descriptive-analytic design with a cross-sectional approach was employed. The study population consisted of adults living in X area, with a total sample of 150 respondents selected using purposive sampling. Data were collected using a standardized questionnaire covering knowledge, attitudes, and preventive practices related to diabetes mellitus. Data were analyzed using the chi-square test to examine relationships between variables. The results showed a significant association between knowledge level and preventive practices of diabetes mellitus (p < 0.05), as well as a positive association between attitudes and preventive practices (p < 0.05). This study concludes that higher knowledge and positive attitudes are associated with better preventive practices against diabetes mellitus. These findings are expected to serve as a basis for designing more effective community health education programs to reduce the risk of diabetes mellitus.